2016
DOI: 10.1016/j.neulet.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Lithium effects on circadian rhythms in fibroblasts and suprachiasmatic nucleus slices from Cry knockout mice

Abstract: Lithium is widely used as a treatment of bipolar disorder, a neuropsychiatric disorder associated with disrupted circadian rhythms. Lithium is known to lengthen period and increase amplitude of circadian rhythms. One possible pathway for these effects involves inhibition of glycogen synthase kinase-3β (GSK-3β), which regulates degradation of CRY2, a canonical clock protein determining circadian period. Although there is no evidence that GSK-3β directly phosphorylates CRY1, it is known to play important roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Second, we found that chronic GSK3 inhibition shortened the cycle of the hippocampal molecular clock, consistent with evidence in other mammalian cell types and brain areas (Besing et al, ; Hirota et al, ; Li, Lu, Beesley, Loudon, & Meng, ). Although it is well documented that the GSK3 inhibitor lithium lengthens the period of circadian rhythms (Abe, Herzog, & Block, ; Dokucu, Yu, & Taghert, ; Hirota et al, ; Iwahana, Hamada, Uchida, & Shibata, ; LeSauter & Silver, ; Li et al, ; Mason & Biello, ; Mohawk, Miranda‐Anaya, Tataroglu, & Menaker, ; Noguchi, Lo, Diemer, & Welsh, ; Osland et al, ), our results with a more selective GSK3 inhibitor suggest that lithium‐induced effects may be due to other nonspecific targets such as inositol phosphatase inhibition (Quiroz, Gould, & Manji, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we found that chronic GSK3 inhibition shortened the cycle of the hippocampal molecular clock, consistent with evidence in other mammalian cell types and brain areas (Besing et al, ; Hirota et al, ; Li, Lu, Beesley, Loudon, & Meng, ). Although it is well documented that the GSK3 inhibitor lithium lengthens the period of circadian rhythms (Abe, Herzog, & Block, ; Dokucu, Yu, & Taghert, ; Hirota et al, ; Iwahana, Hamada, Uchida, & Shibata, ; LeSauter & Silver, ; Li et al, ; Mason & Biello, ; Mohawk, Miranda‐Anaya, Tataroglu, & Menaker, ; Noguchi, Lo, Diemer, & Welsh, ; Osland et al, ), our results with a more selective GSK3 inhibitor suggest that lithium‐induced effects may be due to other nonspecific targets such as inositol phosphatase inhibition (Quiroz, Gould, & Manji, ).…”
Section: Discussionmentioning
confidence: 99%
“…For measuring luminescence rhythms from explants, we placed the sealed 35‐mm culture dishes into a luminometer (LumiCycle, Actimetrics, Inc., Wilmette, IL), inside a standard tissue culture incubator set at 35°C, dry, 0% CO 2 . Luminescence from each dish was measured by a photomultiplier tube for 70 s at intervals of 10 min and recorded as counts/s over 6 days as described previously (Noguchi, Lo, Diemer, & Welsh, 2016). When the average bioluminescence intensity over 6 days did not exceed 40 counts/s above the background level (10–50 counts/s) or dropped to background level within 4 days, the explant was considered damaged, and was excluded from analysis (59/490 explants).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that similar biological processes may occur in the SCN of mice receiving lithium for a long period of time because lithium imposes a non-24 h circadian period on mice. Second, although brain and blood concentrations of lithium are similar 32 , a few reports, as described above, have indicated that the SCN clock is more sensitive to lithium than peripheral clocks 4,30 , suggesting that a longer period of time is needed to eliminate the effect of lithium on the SCN clock compared to peripheral clocks. The incomplete reversibility of the effect of lithium on circadian period length in locomotor activity observed in the previous report may be due to prolonged aftereffects on the SCN clock.…”
Section: Discussionmentioning
confidence: 94%
“…Given that the therapeutically effective concentration of lithium in serum (approximately 0.5–1.5 mM) is lower than the IC50 of lithium for the inhibition of GSK3β (approximately 2 mM) 29 , inhibition of GSK3β by lithium at therapeutic levels may also be insufficient to contribute significantly to mood stabilization. Although a few reports indicated that low doses of lithium (1–2 mM) lengthen circadian period elongation in the suprachiasmatic nucleus (SCN) under ex vivo culture conditions 4,30 , this conclusion remain controversial 5 . The effect of lithium on core-clock gene expression, particularly of peripheral clocks, has not yet been investigated in vivo because, as already explained, detection of changes in period length in vivo using traditional experimental approaches is technically difficult.…”
Section: Discussionmentioning
confidence: 99%